Examining the growth of cycling in Dublin - CAULFIELD, BRIAN (My University, 2013)
In the past few decades much research has been conducted on the increasing numbers of commuters taking up cycling to work. This modal shift has been encouraged by pro-cycling policies to increase the attractiveness of cycling and the construction of new cycling infrastructure. In Dublin, several policies have been applied such as a bike rental scheme, bicycle - purchasing schemes, reducing speed limits and the construction of segregated cycle lanes to promote cycling. This paper seeks to examine what, if any, impact these policies have had on cycling rates in Dublin. The paper compares census data from 2006 and 2011 to determine how cycling rates have changed and if the demographics of cyclists have changed in the city. The results presented in the paper show that cycling rates have increased in Dublin and that more females, those in higher age and socio-economic groups are cycling to work on a regular basis.
ITRN
PUBLISHED
TCD
Keywords: Cycling; Smart & Sustainable Planet; CYCLING